Pentingnya Berpikir Komputasional dalam Pembelajaran Matematika - Sabinus Rainer N. Christi; Widyawanti Rajiman (Journal on Education, 2023)
Computational thinking is a way of thinking that refers to the ability to solve problems using the concepts used in computing. These concepts include systematic problem solving, data analysis, algorithms, abstraction, and information representation. The method used in this research is library research. Computational thinking not only helps us acquire computer-related skills, but can also enhance our ability to solve problems in other domains. Several studies have found that computational thinking is beneficial for improving mathematical abilities, reasoning abilities, and creative thinking.